2014
DOI: 10.1016/j.ijpharm.2014.07.056
|View full text |Cite
|
Sign up to set email alerts
|

Molecular expression and functional activity of vitamin C specific transport system (SVCT2) in human breast cancer cells

Abstract: The main goal of this study is to investigate the expression of sodium dependent vitamin C transport system (SVCT2). Moreover this investigation has been carried out to define uptake mechanism and intracellular regulation of ascorbic acid (AA) in human breast cancer cells (MDA-MB231, T47D and ZR-75-1). Uptake of [14C] AA was studied in MDA-MB231, T47D and ZR-75-1 cells. Functional parameters of [14C] AA uptake were delineated in the presence of different concentrations of unlabeled AA, pH, temperature, metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…Consistent with these results, the study of Varun et al. [35] showed that radiolabeled AA uptake in breast cancer cells was significantly inhibited in the presence of unlabeled AA, whereas no substantial alteration in the uptake was observed with unlabeled DHA.…”
Section: Discussionsupporting
confidence: 69%
“…Consistent with these results, the study of Varun et al. [35] showed that radiolabeled AA uptake in breast cancer cells was significantly inhibited in the presence of unlabeled AA, whereas no substantial alteration in the uptake was observed with unlabeled DHA.…”
Section: Discussionsupporting
confidence: 69%
“…The higher susceptibility of cancer cells to M/A could be also explained by the higher ascorbate and/or menadione uptake compared to normal cells [ 67 , 87 , 88 ]. It is well known that vitamin C transporters are overexpressed on the plasmatic and outer mitochondrial membranes of many types of cancer cells [ 67 , 87 , 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al 6 reported no correlations between vitamin C-induced cell death and GSH, catalase, or GPx activities. Meanwhile, the vitamin C transporter was involved in the sensitivity of breast cancer cells to vitamin C 21 22 . Furthermore, hypoxic conditions (1% O 2 ) suppressed the cytotoxicity of vitamin C more in 60 cancer cell lines than normoxic conditions (21% O 2 ) did 23 .…”
Section: Discussionmentioning
confidence: 99%